Fundamentals of mold growth in indoor environments and strategies for healthy living - Adan, Olaf C. G.; Samson, Robert A.; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers : Imprint: Wageningen Academic Publishers, 2011)
Today, indoor mold and moisture, and their associated health effects, are a society-wide problem. The economic consequences of indoor mold and moisture are enormous. Their global dimension has been emphasized in several recent international publications, stressing that the most important means for avoiding adverse health effects is the prevention (or minimization) of persistent dampness and microbial growth on interior surfaces and in building structures. This book aims to describe the fundamentals of indoor mold growth as a prerequisite to tackle mold growth in the existing building stock as well as in future energy efficient buildings. It brings together different disciplinary points of view on indoor mold, ranging from physics and material science to microbiology and health sciences. The contents have been outlined according to three main issues: Fundamentals, particularly addressing the crucial roles of water and materials, Health, including a state-of-the-art description of the health-related effects of indoor molds, and Strategies, integrating remediation, prevention and policies.
Preface -- 1. Introduction; O.C.G. Adan, R.A. Samson -- 2. Water relations of fungi in indoor environments; O.C.G. Adan et al -- 3. Fungal growth and humidity fluctuations: a toy model; H.P. Huinink, O.C.G. Adan -- 4. The fungal cell; J. Dijksterhuis -- 5. Ecology and general characteristics of indoor fungi; R.A. Samson -- 6. Characteristics and identification of indoor wood-decaying basidiomycetes; O. Schmidt, T. Huckfeldt -- 7. Health effects from mold and dampness in housing in western societies: early epidemiology studies and barriers to further progress; J.D. Miller -- 8. Aerosolized fungal fragments; B.J. Green et al -- 9. Mycotoxins on building materials; K.F. Nielsen, J.C. Frisvad -- 10. WHO guidelines for indoor air quality: dampness and mold; O.O. Hänninen -- 11. Moisture content measurement; B.J.F. Erich, L. Pel -- 12. The fungal resistance of interior finishing materials; O.C.G. Adan -- 13. Detection of indoor fungi bioaerosols; J.A. Scott et al -- 14. Mold remediation in North American buildings; P.R. Morey -- 15. Mold remediation in West-European buildings; T. Warscheid -- 16. Protection of wood; M.F. Sailer, W.J. Homan -- 17. Coating and surface treatment of wood; H. Viitanen, A.-C. Ritschkoff -- 18. Recommendations; O.C.G. Adan, R.A. Samson -- Contributors -- Index.
Keywords: Life sciences; Botany; Life Sciences; Life Sciences, general; Plant Sciences